Generic prescription drug price increases: which products will be affected by proposed anti-gouging legislation? - Rena M. Conti; Kevin H. Nguyen; Meredith B. Rosenthal (Taylor & Francis Group, 2018)
Background In the United States (U.S.), large price increases for selected generic drugs have elicited public outrage. Recent legislative proposals aim to increase price transparency and identify outlier drug "price spikes." It is unknown how many and what types of products would be highlighted by such efforts. Methods IQVIA Health Incorporated's National Sales Perspectives™ provided sales, use and price data for all generic prescription products (unique molecule-manufacturer-formulation combinations) sold in the U.S. We estimated annual prescription price levels and changes between 2013 and 2014. We identify drugs with annual prescription price increases in excess of the medical consumer price index (CPI), and in excess of 15% or 20%, per legislative proposals. We reported annualized inflation-adjusted mean, standard deviation (SD), median, and 95th percentile prescription price increases and percentage of products exceeding the growth in the medical CPI. We fitted logistic regression models to identify characteristics of drugs associated with each category of price increase. Results We analyzed data for 6,182 generic products. The mean inflation-adjusted price increase among all generic products was 38% (SD 1,053%), the median, 2%; the 95th percentile, 135%; and the mean price level, $29.69 (SD $378.44). Approximately half of all products experienced price increases in excess of the growth in the medical CPI; 28% had price increases greater than 15% and 23% had price increases greater than 20%. Drugs exceeding outlier thresholds exhibited lower baseline price levels than the mean price level observed among all generic drugs. The most consistent characteristic predicting whether a product would exceed "price spike" thresholds proposed in legislation is the being supplied by only one manufacturer. Conclusions "Price spikes" among generic drugs in 2014 were more common than newspaper stories and legislative hearings suggest. While the cross-sectional association between an indicator of being sold by only a single manufacturer and the probability of meeting specific price growth thresholds is suggestive of an economically intuitive causal story, future work should delve more deeply into whether decreases in generic competition explain the dramatic price increases that have captured the public's attention in recent years.